Molecular pathology of X linked retinoschisis: mutations interfere with retinoschisin secretion and oligomerisation. Issue 1 (16th December 2005) - Wang, T; Zhou, A; Waters, C T; O'Connor, E; Read, R J; Trump, D
Abstract : Background/aim: X linked retinoschisis (XLRS) is caused by mutations in RS1 which encodes the discoidin domain protein retinoschisin, secreted by photoreceptors and bipolar cells. Missense mutations occur throughout the gene and some of these are known to interfere with protein secretion. This study was designed to investigate the functional consequences of missense mutations at different locations in retinoschisin. Methods and results: The authors developed a structural model of the retinoschisin discoidin domain and used this to predict the effects of missense mutations. They expressed disease associated mutations and found that those affecting conserved residues prevented retinoschisin secretion. Most of the remaining mutations cluster within a series of loops on the surface of the β barrel structure and do not interfere with secretion, suggesting this region may be a ligand binding site. They also demonstrated that wild type retinoschisin octamerises and associates with the cell surface. A subgroup of secreted mutations reduce oligomerisation (C59S, C219G, C223R). Conclusions: It is suggested that there are three different molecular mechanisms which lead to XLRS: mutations interfering with secretion, mutations interfering with oligomerisation, and mutations that allow secretion and oligomerisation but interfere with retinoschisin function. The authors conclude that binding of oligomerised retinoschisin at the cell surface is important in its presumed role in cell adhesion.